Efficacy and safety of Shen Gui capsules for chronic heart failure: a systematic review and meta-analysis - Yan, Jiaqi; Zhang, Chaorong; Wang, Yuanping; Yan, Xia; Jin, Lili (Frontiers in Pharmacology, 2024)
Background: Although Shen Gui capsules (SGCP) are widely used as an adjuvant treatment for chronic heart failure (CHF), their clinical efficacy and safety remain controversial.Purpose: To assess the efficacy and safety of SGCP in the treatment of CHF through a systematic review and meta-analysis, to provide high-quality evidence for evidencebased medicine.Methods: Seven databases were searched for randomized controlled trials (RCTs) assessing SGCP for CHF, from inception to January 9, 2023. RCT quality of evidence was evaluated using the Cochrane Handbook for the Evaluation of Intervention Systems to assess risk of bias and Grading of Recommendations Assessment, Development, and Evaluation. A meta-analysis with subgroup and sensitivity analyses was performed using Review Manager 5.4 and Stata 12.Results: Nine RCTs representing 888 patients with CHF were included in the review.Meta-analysis revealed that SGCP combined with conventional heart failure therapy is more advantageous for improving left ventricular ejection fraction [LVEF; mean difference (MD)=5.26, 95% confidence interval (CI) (3.78, 6.74), P<0.0000] and increasing effective rate [relative risk (RR)=1.21, 95%CI (1.14, 1.29), P<0.001] compared with conventional therapy alone. The experimental treatment also reduced brain natriuretic peptide , P=0.0007], left ventricular end-diastolic diameter [MD=-1.93, 95%CI (-3.22, -0.64), P=0.003], and hypersensitive C-reactive protein [MD=-2.70, 95%CI (-3.12,-2.28), P<0.001] compared with the control group. However, there was not a statistically significant difference in tumor necrosis factor-α [ 5.73), P=0.16] or left ventricular end-systolic diameter [MD=-1.56, 95%CI (-3.13, 0.01), P=0.05]. Nor was there a statistically significant between-groups difference in incidence of adverse events (P>0.05).LVEF and increase the effective rate to safely treat patients with CHF. However, further high-quality studies are needed to confirm these findings, due to the overall low quality of evidence in this literature.